2000
DOI: 10.1086/302996
|View full text |Cite
|
Sign up to set email alerts
|

A Sensitive Denaturing Gradient-Gel Electrophoresis Assay Reveals a High Frequency of Heteroplasmy in Hypervariable Region 1 of the Human mtDNA Control Region**Disclaimer: The opinions and assertions expressed herein are solely those of the authors and are not to be construed as official or the views of the United States Department of Defense, the United States Department of the Army, or the United States Department of Commerce. This paper is a contribution of the United States National Institute of Standa

Abstract: A population study of heteroplasmy in the hypervariable region 1 (HV1) portion of the human mtDNA control region was performed. Blood samples from 253 randomly chosen individuals were examined using a sensitive denaturing gradient-gel electrophoresis (DGGE) system. This method is capable of detecting heteroplasmic proportions as low as 1% and virtually all heteroplasmy where the minor component is > or = 5%. Heteroplasmy was observed in 35 individuals (13.8%; 95% confidence interval [CI] 9.6-18.0). Of these in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(19 citation statements)
references
References 55 publications
3
14
0
Order By: Relevance
“…Examination of the position-specific incidence of PHP in the CR and the codR reported in this study (obtained from Additional File 9 in [42] , and displayed in part in Table S2) reveals some highly unusual patterns. For instance, 21 positions, including multiple coding region positions, have a higher frequency of PHP than position 16,093 – which past studies have repeatedly demonstrated has the highest rate of PHP in the CR [10,18,19,68,71,80] . As an extreme example, the number of PHP reported for position 513 was more than 8-fold greater than the incidence of PHP at 16,093; yet in an earlier, Sanger-based study of heteroplasmy in more than 5000 CR haplotypes, not a single instance of PHP at position 513 was detected [19] .…”
Section: Incidence and Pattern Of Human Mtdna Heteroplasmy In Sanger mentioning
confidence: 99%
See 1 more Smart Citation
“…Examination of the position-specific incidence of PHP in the CR and the codR reported in this study (obtained from Additional File 9 in [42] , and displayed in part in Table S2) reveals some highly unusual patterns. For instance, 21 positions, including multiple coding region positions, have a higher frequency of PHP than position 16,093 – which past studies have repeatedly demonstrated has the highest rate of PHP in the CR [10,18,19,68,71,80] . As an extreme example, the number of PHP reported for position 513 was more than 8-fold greater than the incidence of PHP at 16,093; yet in an earlier, Sanger-based study of heteroplasmy in more than 5000 CR haplotypes, not a single instance of PHP at position 513 was detected [19] .…”
Section: Incidence and Pattern Of Human Mtdna Heteroplasmy In Sanger mentioning
confidence: 99%
“…There are a few notable exceptions, however. In particular, PHP at position 16,093 has often been observed at rates more than double any other CR position, despite a substitution rate that is considerably lower than other variable sites in the CR [7,23,71–73] .…”
Section: Incidence and Pattern Of Human Mtdna Heteroplasmy In Sanger mentioning
confidence: 99%
“…On the other hand, it should be stressed that analysis of mtDNA segregation in tissues other than blood was not possible in the case of the individuals examined in the present study. Moreover, direct sequencing itself is not capable of detecting heteroplasmic variants occurring at low proportions (Tully et al, 2000). Thus, the question of the impact of the Y831C mutation on mtDNA condition remains open.…”
Section: Discussionmentioning
confidence: 99%
“…[5], [6]). With increasing numbers of analyzed samples as well as improvements in detection chemistries and instrumentation it became clear that heteroplasmy occurs (also in individuals unaffected by mitochondrial disorders) at considerably higher rates than originally assumed [7], [8], [9], [10]. Heteroplasmy not only has the potential to put extra weight on haplotypes by increasing the overall (forensic) information content of a particular haplotype [11], but also plays a paramount role for mtDNA evolution as well as the understanding and diagnosis of mitochondrial diseases.…”
Section: Introductionmentioning
confidence: 99%